1994
DOI: 10.1007/bf02087539
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol is effective treatment for patients with severe chronic constipation

Abstract: To assess the efficacy of misoprostol in the treatment of patients with severe chronic constipation, nine such patients were enrolled in a double-blind, randomized, crossover study of misoprostol (1200 micrograms/day) or placebo, that lasted three weeks. During this period each patient received the drug for one week and placebo for another with a week washout period in between. A colonic transit study, using radiopaque markers, was performed during each of the treatment weeks, while the number of stools and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 23 publications
0
37
0
2
Order By: Relevance
“…In adults, management may be more challenging than increased frequency and weight of bowel movements in adults with severe chronic constipation [44]. There have in children.…”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…In adults, management may be more challenging than increased frequency and weight of bowel movements in adults with severe chronic constipation [44]. There have in children.…”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…Other drugs used in patients with constipation not responding to standard medications are: prostaglandin E 1 analogue, misoprostol [69], and microtubule formation inhibitor, colchicines [70]. It is important to remember that misoprostol cannot be used during pregnancy and should be used cautiously in reproductive age women who could become pregnant because of effects on uterine contractility and risk of abortion.…”
Section: Treating Other Functional Bowel Disordersmentioning
confidence: 99%
“…Soffer et al did report in 1994, that in nine patients with RCC, misoprostol could be shown to signi®cantly increase the weight and frequency of bowel movements with an associated decrease in colonic transit time when administered during a 1-week trial. 16 It was not known, however, if this effect could be sustained over a long period or if the response was transitory. We found mixed results with our outpatient population.…”
Section: ±24mentioning
confidence: 99%
“…In a shortterm clinical trial colonic transit time decreased and faecal weight increased in patients with severe refractory chronic constipation (RCC) given misoprostol over 1 week. 16 However, there are no published data regarding the long-term clinical outcome of RCC patients treated with misoprostol. The aim of this study was to determine the short-and long-term effects of misoprostol in patients with severe RCC as demonstrated by post-prandial colonic myoelectical activity, colonic transit time and clinical response.…”
mentioning
confidence: 99%